Creative Schools : The Grassroots Revolution That's Transforming Education - Robinson, Ken, 1950-; Aronica, Lou. (New York : Viking, 2015)
At a time when standardized testing businesses are raking in huge profits, when many schools are struggling, and students and educators everywhere are suffering under the strain, Ken Robinson argues for an end to our outmoded industrial educational system. He proposes instead a highly personalized, organic approach that draws on today's unprecedented technological and professional resources to engage all students, develop their love of learning, and enable them to face the real challenges of the twenty-first century. Filled with anecdotes, observations, and recommendations from professionals on the front line of transformative education, case histories, and groundbreaking research, Creative Schools aims to inspire teachers, parents, and policy makers alike to rethink the real nature and purpose of education.
Introduction: One minute to midnight -- Back to basics -- Changing metaphors -- Changing schools -- Natural born learners -- The art of teaching -- What's worth knowing? -- Testing, testing -- Principles for principals -- Bring it all back home -- Changing the climate.
Includes bibliographical references and index.
Text in English.
Keywords: Creative thinking -- Study and teaching -- United States; Creative ability -- Study and teaching -- United States; Educational change -- United States; School improvement programs -- United States; Education / Teaching; Educational Policy & Reform; Aims & Objectives; Administration - General